Monitoring of the Sensitivity In Vivo of Plasmodium falciparum to Artemether-Lumefantrine in Mali - Modibo Diarra; Drissa Coulibaly; Amadou Tapily; Boureima Guindo; Koualy Sanogo; Diakalia Koné; Youssouf Koné; Karim Koné; Aboudramane Bathily; Oumar Yattara; Mahamadou A. Thera; Alassane Dicko; et al. (Tropical Medicine and Infectious Disease, 2021)
In Mali, since 2007, artemether-lumefantrine has been the first choice against uncomplicated malaria. Despite its effectiveness, a rapid selection of markers of resistance to partner drugs has been documented. This work evaluated the treatment according to the World Health Organization’s standard 28-day treatment method. The primary endpoint was the clinical and parasitological response corrected by a polymerase chain reaction. It was more than 99.9 percent, the proportion of patients with anemia significantly decrease compared to baseline (p < 0.001), and no serious events were recorded. Plasmodium falciparum remains sensitive to artemether-lumefantrine in Mali.